Predictive Factors of Thoracic Lymph Node Metastasis Accompanying Pulmonary Metastasis from Colorectal Cancer - Ali, Kamran; Cho, Sukki; Jang, Hyo Jun; Kim, Kwhanmien; Jheon, Sanghoon (The Thoracic and Cardiovascular Surgeon, 2019)
Background The aim of this study was to identify the factors predicting thoracic lymph node (LN) metastases for pulmonary resection from colorectal cancer (CRC).Methods The records of 160 patients who underwent pulmonary metastasectomy for CRC were retrospectively reviewed. Clinicopathologic factors were analyzed with chi-square test or t-test and logistic regression to identify predictable factors for LN metastases.Results Sixty patients (37.5%) underwent LN dissection during pulmonary metastasectomy, and LN metastases were found in five patients. Twenty-three patients had LN recurrence among the 100 patients (62.5%) without LN dissection during the follow-up period. Twenty-eight patients out of 160 (17.5%) had LN metastases. By multivariate analysis, the number of pulmonary metastasis and metastasis from colon cancers were independent factors predicting LN metastases.Conclusion The number of pulmonary metastasis and metastasis from colon cancers were independent factors predicting LN metastases. LN sampling should be performed especially in cases with strong predictive factors to improve staging and help guide further treatment.
Keywords: metastasectomy; predictable factor; lymph node metastasis